Stamp Technique: An Explorative SEM Analysis - Francesca Zotti; Stefano Vincenzi; Alessandro Zangani; Paolo Bernardi; Andrea Sbarbati (MDPI AG, 2023)
Background: Achieving correct tooth anatomy and saving time at the dental chair are some of the goals of modern restorative dentistry. Stamp technique has gained acceptance in clinical practice. The aim of this study was to evaluate the effectiveness of this technique in terms of microleakage, voids, overhangs and marginal adaptation of Class I restorations, and to analyse the operative times in comparison with traditional restorative procedures. Methods: Twenty extracted teeth were divided into 2 groups. Ten teeth in the study group (SG) were Class I prepared and restored using stamp technique, and ten teeth in the control group (CG) were Class I restored traditionally. SEM analysis was performed to evaluate voids, microleakage, overhangs, and marginal adaptation, and operative times were recorded. A statistical analysis was performed. Results: There were no significant differences in microleakage, marginal adaptation and filling defects between the two groups, however, the stamp technique seems to facilitate the formation of large overflowing margins that require a careful finishing phase. Conclusions: Stamp technique does not seem to have any critical aspects in terms of restoration durability and it can be performed in a short time.